A New Resource for Honeymoon and Associated Uranium Deposits in the Eastern Callabonna Sub-Basin; The Integration of 40 Years of Exporation Drilling. Issue 1 (1st December 2019) - Rao, A; Williams, P K; Abzalov, M Z
Summary: The Honeymoon Uranium Deposits were first discovered in the late 1960's, and since then there has been sporadic exploration, and one concerted attempt to develop the deposit as an In Situ Leach (ISL) operation (2011), when the uranium priced peaked briefly. Ownership of the deposit changed in 2017, and in the last 3 years there has been a systematic effort to bring all the past and recent drill hole information up to a common JORC 2012 Compliant standard, and hence calculate a new JORC Compliant Resource. Much of the geological interpretation has been derived from a series of geophysical logs, and there has been reliance on uranium grades being calculated from prompt fission neutron (PFN) and natural gamma logging. Recent drilling has been focussed on adding additional control and removing ambiguity from historic results. The new Mineral Resource over Honeymoon's Re-start Area now totals 24Mt at 660 ppm U3O8 for 36Mlbs U3O8 (30% increase over previous) and the Global Mineral Resource now stands at 71.6 Mlbs U3O8, 52Mt at 620 ppm U3O8. The increase in resource has been due to a number of important factors; disequilibrium modelling which has improved parity between the eU3O8 gamma data and the pU3O8 PFN data, honouring local variations and trends; introduction of interpreted mineralisation zones to better honour local geology, palaeovalley and palaeo-channel profile, tenor of mineralisation, and disequilibrium characteristics; improved resource classification through additional drilling, PFN data in key areas, localized correction of the gamma data and classification according to confidence issues related to individual mineralised zones, and additional drilling throughout the project area including additional PFN data in key areas of geological and economic significance.